SPACE WEATHERING PROCESSES ON AIRLESS BODIES: FE ISOTOPE FRACTIONATION IN THE LUNAR REGOLITH - Wiesli R.A.; Beard B.L.; Taylor L.A.; Johnson C.M. (My University, 2003)
Nanophase Fe metal grains (np-Fe°) are a product of space weathering, formed by processes related to meteorite impacts, and solar-wind sputtering on airless planetary bodies, such as the Moon. Iron isotopes of lunar soils are fractionated during these processes, and the np-Fe° in the finest (<10 μm), mature, size fractions of the soil become enriched in heavier isotopes by ~0.3‰ 56Fe/54Fe in comparison to the bulk rocks (0.03+/-0.05‰), from which the soil was formed. A positive correlation of δ56Fe values with the soil maturity index, IS/FeO, suggests that the high δ56Fe values reflect production of nanophase Fe metal that is produced by space weathering that occurs on airless planetary bodies. Furthermore, the enrichment of δ56Fe in the smallest size fraction of lunar soils supports a model for creation of np-Fe° through vapor deposition induced by micrometeorites, as well as that by solar-wind sputtering.
Keywords: FE ISOTOPES; ISOTOPE FRACTIONATION; LUNAR SOILS; SPACE WEATHERING